2019
DOI: 10.1177/1757177419833165
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of observational hand hygiene audit with targeted feedback on doctors’ hand hygiene compliance: A retrospective time series analysis

Abstract: Background: Healthcare-associated infection compromises patient safety. Compliance with hand hygiene (HH) guidelines has been shown to be an effective method of reducing infection; however, it remains suboptimal and poorer among doctors compared to other healthcare workers. The aim of this study is to determine the relationship between an individualised observational hand hygiene audit (OHHA) and feedback intervention with observed HH compliance. Methods: We used a retrospective interrupted time series design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Having a sense of urgency seems to be an important precondition for healthcare professionals to engage: if healthcare professionals perceive the current situation as untenable for themselves or for the safety of patients, this will urge them to take action [ 82 , 105 ]. Several studies have described local audits that were started by intrinsically motivated healthcare professionals on issues they felt to impact on patient care [ 48 , 53 , 61 , 63 , 69 , 82 , 88 , 97 , 99 , 103 ]. In contrast, if healthcare professionals perceive an audit as a ‘side-line’ or ‘mandatory exercise’, rather than a process to contribute to improved quality of care, they will not feel engaged and not put significant effort into the change [ 77 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Having a sense of urgency seems to be an important precondition for healthcare professionals to engage: if healthcare professionals perceive the current situation as untenable for themselves or for the safety of patients, this will urge them to take action [ 82 , 105 ]. Several studies have described local audits that were started by intrinsically motivated healthcare professionals on issues they felt to impact on patient care [ 48 , 53 , 61 , 63 , 69 , 82 , 88 , 97 , 99 , 103 ]. In contrast, if healthcare professionals perceive an audit as a ‘side-line’ or ‘mandatory exercise’, rather than a process to contribute to improved quality of care, they will not feel engaged and not put significant effort into the change [ 77 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…We provided real-time performance feedback to non-compliers to raise their awareness of the importance of compliance for patient safety, a strategy that helped raise compliance after every drop, such as seen in November and December 2016, and August 2017. Several previous studies have shown that provision of real-time individual or group feedback was associated with improvement and sustainability of high compliance rates [21][22][23][24], as well as reduction in serious nosocomial infections such as central line-associated blood stream infections [25].…”
Section: Discussionmentioning
confidence: 99%
“…The SMSS can be used to conduct audits and provide feedback to grantees committed to sustaining prevention programs and initiatives once initial funding has ended. are recognized as important for prevention [19,20], much of the relevant science on feedback in health has involved improvement in clinical performance [21][22][23][24][25][26][27]. This includes clinical supervision and use of technology like electronic dashboards in measurement-based quality improvement (MBQI) strategies that monitor patient behavior and clinician activity [28][29][30], while prevention has a more limited history of using computational technologies for monitoring [31][32][33][34].…”
Section: Contributions To the Literaturementioning
confidence: 99%